Impacts caused by the COVID-19 pandemic on users of of Primary Health Care in the Municipality of Cuité-PB (Brazil) (Research, Society and Development, 2022)
This study aims to identify the impacts caused by the COVID-19 pandemic on users of Primary Health Care in the Municipality of Cuité-PB (Brazil).This is an exploratory, descriptive study with a qualitative approach, with users and health professionals of primary health care in the municipality of Cuité-PB. Interviews were conducted with 27 participants and data were analyzed using Bardin's content analysis. The work is part of a major study entitled by meanings attributed by users of primary health care in healthy lifestyle. According to the analysis of the interviews, three categories were elaborated: Discontinuity of the guidelines and actions of healthy practices carried out at the UBS; awakening from emotional problems as a result of future uncertainties caused by the pandemic and Restrictions on healthy and leisure activities. It was possible to understand and realize that health guidelines and actions have decreased in order to avoid crowds in basic units, so care was presented in a restricted way in terms of encouraging healthy practices. Added to this, the population is faced with impasses resulting from confinement and social isolation, which can be considered triggers for the emergence of mental problems. In addition, restrictions on healthy and leisure practices also interfere with users' well-being. Thus, research that addresses this issue through the dissemination of the health needs of users is necessary, as new evidence can expand the possibilities of health interventions, improving the quality of care, as well as subsidizing the reduction of the impacts caused by the disease pandemic.